Insider Trading dan Pelanggaran Atas Prinsip Keterbukaan dalam Pasar Modal - Heykal, Mohamad (Bina Nusantara University, 2013)
Insider trading is a violation in the capital market. When it is ignored it can provide problems for the capital market industry in one country. Instead, the attempt to prove insider trading is difficult; and up to now handling the problems has many made use of the various provisions contained in Law No 8 of 1995. Research through the literature study relating to insider trading shows that insider trading is a violation of the principle of transparency existing in the capital market and is also difficult to prove. This study shows that there are several supporting factors to include insider trading. They are the insiders, material information and having not been announced to the public, as well as internal control weaknesses.